Manajemen Pembelajaran Matematika Di SD Negeri Mangkubumen 83 Surakarta - , Riyanti; , Prof. Dr. Sutama, M.Pd; , Dr. Maryadi, M.A (2017)
The objective of this study are to describe (1) the characteristics of the planning study of mathematics in primary schools Mangkubumen 83 Surakarta; (2) the characteristics of the implementation of mathematics in primary schools Mangkubumen 83 Surakarta; and (3) the characteristics of the mathematics curriculum evaluation in SD Negeri 83 Surakarta Mangkubumen. The research is a qualitative research with ethnographic research design. The location study performed on 83 Mangkubumen SD Negeri Surakarta. Mechanical pengumplan data using in-depth interviews, documentation, and observation. Analysis of the data using three stages: data reduction, data presentation, and drawing conclusions with verification. The results of this study indicate that (1) mathematics learning plan prepared by teachers in groups based on the education unit level curriculum (SBC), developed in accordance with the environmental conditions of each school. Math lesson plans drawn up guidance on learning mathematics with attention to the linkages and coherence between KI and KD, learning materials, learning activities, assessment, and sources belalajar in the integrity of the learning experience. (2) The learning objectives based on the curriculum of mathematics education unit level. Learning material math prepared in accordance with the standards of competence which have been set in the educational unit level curriculum, containing the six (6) standard of competence, divided for the first semester of four (4) standard of competence, and two (2) standard of competence for the second semester. Mathematics teaching methods used by teachers is the deductive method, demonstration, discussion, expository, exercise, and frequently asked questions. Mathematics instructional media types vary, with the aim of explaining the concept of mathematics, both to algebra, arithmetic, odds, statistics, logic, and geometry, adapted to the use of learning materials. Implementation of the learning is done in three stages: the initial stage, the core stage of learning, and the final stage. (3) Evaluation Mathematics curriculum, conducted by the principal during the learning process and the end of the semester by means of observation, documentation and observation. Curriculum evaluation component comprising: a standard assessment content, assessment of learning planning, implementation of learning, assessment standards and graduation standards.